Head and neck cancer surgery during the coronavirus pandemic: a single-institution experience. Issue 2 (1st February 2021) - Jeannon, J-P; Simo, R; Oakley, R; Townley, W; Orfaniotis, G; Fry, A; Arora, A; Taylor, C; Ahmad, I
Abstract: Objective: The coronavirus disease 2019 pandemic resulted in the cessation of elective surgery. The continued provision of complex head and neck cancer surgery was extremely variable, with some UK centres not performing any cancer surgery. During the pandemic, Guy's and St Thomas' NHS Foundation Trust received high numbers of coronavirus disease 2019 admissions. This paper presents our experience of elective complex major head and neck cancer surgery throughout the pandemic. Methods: A head and neck cancer surgery hub was set up that provided a co-ordinated managed care pathway for cancer patients during the pandemic; the Guy's Cancer Centre provided a separate, self-enclosed coronavirus-free environment within the hospital campus. Results: Sixty-nine head and neck cancer patients were operated on in two months, and 13 patients had a microvascular free tissue transfer. Nosocomial infection with coronavirus disease 2019 was detected in two cases (3 per cent), neither required critical care unit admission. Both patients made a complete recovery and were discharged home. There were no deaths. Conclusion: Performing major head and neck surgery, including free flap surgery, is possible during the pandemic; however, significant changes to conventional practice are required to achieve desirable patient outcomes.